DEVELOPMENT OF E-VOTING APPLICATION USING HOMOMORPHIC ENCRYPTION - HARTOPO - NIM : 13513068 , MUHTAR
Now days democratic aspect has been affected by technology, one of the example is electronic voting or electronic based election. E-voting has many advantages. It can increase efficiency of time and cost, and decrease probability of miscounting. But beside the advantages, e-voting system has security risks, two of them are risk of data leakage and risk of data manipulation. Cryptography algorithm can be used to overcome the risks. Homomorphic encryption is an encryption form that allows computation on the cipher text without decrypt it first. Pailier algorithm is one of cryptography algorithms that has homomorphic property. Pailier is partial homomorphic. Pailier is additive homomorphic, which means pailier algorithm allows add operation on its cipher text. E-voting application using homomorphic encryption is developed in this final project. The application has two main part, client side and server side. The client-side application encrypts the election data on the client side before sending it to the server-side application. Server-side application perform homomorphic operation to recapitulate the data. Encryption process in only done at the beginning when the voters finish their vote. Decryption process is only done at the end to see the election result when all recapitulation finish. Data is never decrypted on recapitulation process on the server side. The e-voting application is developed using Java programming language. GUI based client build using Java FX and server (voting place and intermediate level) is developed using spring framework. The EVSSO test result shows that the e-voting application has good quality of security especially in cryptography and compliance with election principles with maturity level 5 and 6.